Ranking Broadband Microwave Absorption Performance of Multilayered Polymer Nanocomposites Containing Carbon and Metallic Nanofillers - Danlée, Yann; Mederos-Henry, Francisco; Hermans, Sophie; Bailly, Christian; Huynen, Isabelle (Frontiers in Materials, 2020)
Because electromagnetic (EM) pollution of the environment is becoming such a pervasive issue, highly efficient solutions for EM protection are being keenly sought for. Our approach provides new avenues to simple, compact, and efficient broadband microwave absorbers designed to cancel EM interferences in the microwave range. The paper demonstrates the potential of a clever organization of nanoscale inclusions (carbon nanotubes, graphene, magnetic metallic nanowires or nanoparticles) in polymer matrices for controlling the propagation of microwaves over a wide range of wavelengths (10−3-10−1 m), focusing on broadband absorption. Controlled architectures of polymer composites loaded with various nanofillers, and in particular layered stacks of composite films enable optimization of the absorption bandwidth while preserving the compactness of the structure. First, various carbon-based and metallic nanofillers are synthesized. Next, nanofillers are dispersed in a polymer matrix thanks to melt polymer processing and dispersion techniques. The absorption characteristics of resulting thin composite slabs are first characterized. Various combinations of superposed slabs are then investigated and modeled in order to optimize the absorption of the resulting multilayers. As innovative approach, the performances of the investigated structures are finally compared with the help of a new figure of merit combining the maximum absorption and its bandwidth.